Taxidermy workshops: differently figuring the working of bodies and bodies at work in the past. Issue 3 (23rd December 2016) - Patchett, Merle
Abstract : Geographers have long demonstrated an interest in charting the geographical and bodily dynamics of work and employment. However, within this scholarship very little attention has been paid to historical geographies of craftwork. This paper seeks to address this deficit while also engaging with the evident and evidentiary methodological issues associated with the historical study of practices worked through the body. To do so, the paper experiments in the recuperation of the working spaces and working practice of three Scottish taxidermists. The creative challenge of this type of recovery work is to ascertain what can conceivably be said from those things that remain to mark the working of bodies and bodies at work at these sites. Yet from curated remainders we glean vital insights into the practices and class politics of 19th‐century natural history enquiry, the silenced agencies of a workshop devastated by the First World War and the more‐than‐human histories of elite blood sports and land ownership in the Scottish Highlands. And this is to emphasise that these materials, even in their textual representation in this paper, count: that they can create knowledge and invite affective experience of the past. Overall the paper seeks to emphasise the serious commitment to conceptual and methodological innovation required when geographers engage in researching bodies (both human and animal) 'at work' in the past.